2022
DOI: 10.3389/fbioe.2022.799610
|View full text |Cite
|
Sign up to set email alerts
|

Developing Smart Nanoparticles Responsive to the Tumor Micro-Environment for Enhanced Synergism of Thermo-Chemotherapy With PA/MR Bimodal Imaging

Abstract: With the development of nanotechnology, a theranostics nanoplatform can have broad applications in multimodal image-guided combination treatment in cancer precision medicine. To overcome the limitations of a single diagnostic imaging mode and a single chemotherapeutic approach, we intend to combat tumor growth and provide therapeutic interventions by integrating multimodal imaging capabilities and effective combination therapies on an advanced platform. So, we have constructed IO@MnO2@DOX (IMD) hybrid nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Hollow nanoplatforms based on manganese (Mn), a metallic element paramagnetic in nature, are currently receiving significant attention in the field of MR-enhanced imaging contrast agents and diagnostic-therapeutic integrated platforms. 38 These platforms provide the advantages of both the hollow structures and the intrinsic diagnostic and therapeutic properties of Mn2 + . Empty spaces in particular can contain various small-molecule medications.…”
Section: Nano-contrast Agents In Mrmentioning
confidence: 99%
See 2 more Smart Citations
“…Hollow nanoplatforms based on manganese (Mn), a metallic element paramagnetic in nature, are currently receiving significant attention in the field of MR-enhanced imaging contrast agents and diagnostic-therapeutic integrated platforms. 38 These platforms provide the advantages of both the hollow structures and the intrinsic diagnostic and therapeutic properties of Mn2 + . Empty spaces in particular can contain various small-molecule medications.…”
Section: Nano-contrast Agents In Mrmentioning
confidence: 99%
“…Danafar et al 37 Superparamagnetic substances can decrease T2 relaxation time and boost a low T2 signal to a certain degree. Luo et al 38 created a nanoplatform consisting of IO@MnO 2 @DOX (IMD) hybrid NPs composed of superparamagnetic IO (SPION), manganese dioxide (MnO 2 ), and doxorubicin (DOX). They found that its use allows efficient T2-weighted MRI and switchable photoacoustic (PA) imaging.…”
Section: Magnetic and Superparamagnetic Nano Mri Contrast Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, it has been found that manganese dioxide nanoparticles (MDN) has good biocompatibility, adjustable structure, ability to carry drugs, and the ability to react with GSH or H 2 O 2 to reduce Mn 4+ to Mn 2+ . The resulting Mn 2+ enhances the ability of T1-weighted MRI [ 18 ] [ 19 ] [ 20 ]. Most of the previously reported MDN are nano-flake and particle structure, which may not be ideal for drug loading and effective release [ 21 ] [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28] Our group also reported a MnO 2based TME-responsive nanoprobe for multimodal imaging. 29 However, most of the reported MnO 2 nanostructures were nanosheets or nanocomposites combined with other nanoparticles, which might not achieve the desired drug-loading effect. 30,31 Therefore, the development of structures with large specific surface areas, robust structures, and sufficient drugloading capacity remains a top priority.…”
Section: Introductionmentioning
confidence: 99%